Expression of the Antimicrobial Peptide SE-33-A2P, a Modified Analog of Cathelicidin, and an Analysis of Its Properties - Vagif Gasanov; Ekaterina Vorotelyak; Andrey Vasiliev (MDPI AG, 2024)
In this study, we developed a method for the expression of the antimicrobial peptide SE-33-A2P in E. coli bacterial cells. The SE-33-A2P peptide consists of A2P and SE-33 peptides and is a retro analog of cathelicidin possessing antimicrobial activity against both Gram-positive and Gram-negative bacteria. Furthermore, the A2P peptide is a self-cleaving peptide. For an efficient expression of the SE-33-A2P peptide, a gene encoding several repetitive sequences of the SE-33 peptide separated by A2P sequences was created. The gene was cloned into a plasmid, with which E. coli cells were transformed. An induction of the product expression was carried out by IPTG after the cell culture gained high density. The inducible expression product, due to the properties of the A2P peptide, was cleaved in the cell into SE-33-A2P peptides. As the next step, the SE-33-A2P peptide was purified using filtration and chromatography. Its activity against both Gram-positive and Gram-negative bacteria, including antibiotic-resistant bacteria, was proved. The developed approach for obtaining a prokaryotic system for the expression of a highly active antimicrobial peptide expands the opportunities for producing antimicrobial peptides via industrial methods.